A ropy exopolysaccharide producing strain Bifidobacterium longum subsp. longum YS108R alleviates DSS-induced colitis by maintenance of the mucosal barrier and gut microbiota modulation. Issue 3 (26th February 2019) - Yan, Shuang; Yang, Bo; Zhao, Jichun; Zhao, Jianxin; Stanton, Catherine; Ross, R. Paul; Zhang, Hao; Chen, Wei
Abstract : Ropy-EPS producing strain YS108R alleviated DSS-induced colitis by anti-inflammation, maintenance of the mucosal barrier and reverting the change of microbiota. Abstract : B. longum has been reported to exert an alleviative effect on colitis, but the results also suggested significant differences among strains. Here in this study, we compared the effect of B. longum subsp. longum strains with different properties in EPS production on DSS-induced colitis. To investigate the alleviative effect of a ropy-exopolysaccharide (EPS) producing strain, Bifidobacterium longum subsp. longum YS108R, on experimental colitis, C57BL/6J mice (male, 6–8 weeks old) were randomly assigned to six groups ( n = 8): normal control, DSS colitis and four DSS colitis groups orally administered with three B. longum subsp. longum strains (YS108R, C11A10B and HAN4-25) and B. animalis subsp. lactis BB12, respectively, in which YS108R produced ropy-EPS, C11A10B produced non-ropy-EPS, HAN4-25 did not produce EPS and BB12 was set as a positive control. Ropy-EPS producing strain YS108R could alleviate the symptoms and remit inflammation induced by DSS, in which YS108R could decrease the pro-inflammatory cytokine IL-6 and IL-17A levels after DSS challenge (from 102 ± 45.22 to 37.95 ± 20.33 pg mL −1 and from 22.14 ± 5.43 to 12.58 ± 2.74, p < 0.05), but another non-ropy-EPS producing strain C11A10B did not decrease the levels of these pro-inflammatory cytokines. Furthermore, YS108R could maintain the expression levels of genes related to the mucosal barrier, but strain HAN4-25, a non-EPS producer, was not able to maintain the expression levels of these genes after DSS challenge. Analysis of gut microbiota showed that DSS treatment significantly increased the relative abundance of Enterobacteriaceae and Peptostreptococcaceae (0.2623 ± 0.162 and 0.0512 ± 0.0361) and decreased the relative abundance of S24-7 (0.042 ± 0.0326); however, YS108R administration could decrease the relative abundance of Enterobacteriaceae and Peptostreptococcaceae to 0.0848 ± 0.0399 and 0.0032 ± 0.0047 and increase the relative abundance of S24-7 to 0.2625 ± 0.0566 ( p < 0.05). The results showed that B. longum subsp. longum YS108R could alleviate DSS-induced colitis by modulating the inflammation related cytokines, maintenance of the normal mucosal barrier and reverting the change of microbiota.